1998
DOI: 10.1161/01.str.29.7.1423
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Basal and Postischemic Leukocyte-Endothelial Adherence by Nitric Oxide

Abstract: Background and Purpose-Recent studies indicate that leukocytes are important contributors to secondary vascular and parenchymal injury after cerebral ischemia. The present study was undertaken to define nitric oxide (NO)Ϫbased mechanisms that regulate leukocyte-endothelial interactions in the cerebral vasculature, how these mechanisms are affected by cerebral ischemia, and whether NO-based therapies can affect postischemic leukocyte dynamics. Methods-Leukocyte adherence to pial venules of anesthetized newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 53 publications
0
29
1
Order By: Relevance
“…By contrast, nitric oxide synthase inhibition augments and prolongs postischemic leukocyte adhesion by mechanisms thought to involve principally a decrease in velocity or shear rate, 46 although others have suggested that nitric oxide exerts a chronic antiadherent effect in the cerebral microcirculation by inactivating adhesionpromoting superoxide radical formation. 47 The latter observation is pertinent here in that serum albumin, via its free sulfhydryl group, reacts with oxides of nitrogen to form a stable S-nitrosothiol with properties resembling endotheliumderived relaxing factor. 48 By this means, albumin may both affect vascular tone and exert antiplatelet effects within the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, nitric oxide synthase inhibition augments and prolongs postischemic leukocyte adhesion by mechanisms thought to involve principally a decrease in velocity or shear rate, 46 although others have suggested that nitric oxide exerts a chronic antiadherent effect in the cerebral microcirculation by inactivating adhesionpromoting superoxide radical formation. 47 The latter observation is pertinent here in that serum albumin, via its free sulfhydryl group, reacts with oxides of nitrogen to form a stable S-nitrosothiol with properties resembling endotheliumderived relaxing factor. 48 By this means, albumin may both affect vascular tone and exert antiplatelet effects within the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring only resting leukocyte behavior, Gidday et al 16 reported an increase in pial venular leukocyte adhesion in newborn pigs in the presence of acute NOS inhibition. In contrast, other investigators have reported no changes in basal leukocyte adhesion in rat pial venules after NOS inhibitor administration, 13,17 although in 1 of those studies 13 the proadhesive actions of leukotriene B 4 were enhanced in the presence of NOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the brain vasculature 13,16,17 involved acute NOS blockade paradigms, whereas ovariectomy is essentially a model of chronic eNOS repression. In the peripheral circulation, chronic inhibition of basal release of NO induces adhesion molecule expression, 18 indicative of a tonic anti-inflammatory role of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide produced by neutrophils and endothelial cells during reperfusion promotes adherence, but it is inactivated by binding to nitric oxide (37). During cerebral ischemia there is an inhibition of nitric oxide production which enhances neutrophil-endothelial adherence (38).…”
Section: Neutropenia Onset and Neuroprotectionmentioning
confidence: 99%